Living in the forest : contemporary houses in the woods - Pearson, Tessa (Phaidon Press, 2022)
Take a walk through luscious jungles, get lost among snowy evergreens and look out from mossy banks across vast Nordic fjords in Living in the Forest, a dynamic survey of contemporary forest homes. Each architect-designed house, whether demonstrating innovative ecological design or shoring against the elements, explores a different facet of woodland living across a huge range of countries worldwide. The properties are shown throughout the book via stunning exterior and interior photography, and each home is accompanied by an illuminating text to bring the property to life. Connecting us to nature through their affinity with trees, each home in this expertly curated collection powerfully demonstrates the importance of green living. Includes outstanding homes by Helen & Hard, HW Studio, Olson Kundig, Studio MK27 and Studio Saxe alongside emerging studios specializing in environmental design. Showcases beautiful houses located in forests around the world, from Australia, Botswana, Brazil, Canada, Iceland, Japan, Mexico, Norway and Thailand as well as the United Kingdom and United States. Explores unique residences, including a playful treehouse built at a spectacular height, an ingenious sustainable hideaway that leaves no footprint and an urban dwelling boasting an biodiverse jungle ecosystem of its own making.